Massive Anisotropic Thermal Expansion and Thermo-Responsive Breathing in Metal-Organic Frameworks Modulated by Linker Functionalization - Henke, Sebastian; Schneemann, Andreas; Fischer, Roland A. (Advanced functional materials, 2013)
Functionalized metal–organic frameworks (fu‐MOFs) of general formula [Zn2(fu‐L)2dabco]n show unprecedentedly large uniaxial positive and negative thermal expansion (fu‐L = alkoxy functionalized 1,4‐benzenedicarboxylate, dabco = 1,4‐diazabicyclo[2.2.2]octane). The magnitude of the volumetric thermal expansion is more comparable to property of liquid water rather than any crystalline solid‐state material. The alkoxy side chains of fu‐L are connected to the framework skeleton but nevertheless exhibit large conformational flexibility. Thermally induced motion of these side chains induces extremely large anisotropic framework expansion and eventually triggers reversible solid state phase transitions to drastically expanded structures. The thermo‐responsive properties of these hybrid solid–liquid materials are precisely controlled by the choice and combination of fu‐Ls and depend on functional moieties and chain lengths. In principle, this combinatorial approach allows for a targeted design of extreme thermo‐mechanical properties of MOFs addressing the regime between crystalline solid matter and the liquid state. Extremely large thermal expansion is shown by pillared‐layered metal–organic frameworks (MOFs) exhibiting alkoxy‐functionalized 1,4‐benzenedicarboxylate linkers. At a certain threshold temperature the materials reversibly switch from a narrow pore to large pore form. This unprecedented thermo‐mechanical behavior is an intrinsic property of the materials and can be modulated substantially by mixing differently functionalized linkers to obtain mixed linker MOF solid solutions.